PENEGAKAN HUKUM OLEH KOMISI PENGAWASAN PERSAINGAN USAHA (KPPU) DALAM PERJANJIAN INTI PLASMA PERKEBUNAN KELAPA SAWIT - Ageng Triganda Sayuti; Busyra Azheri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Abstract: The MSME Law states that the implementation of partnerships is supervised in an orderly and regular manner by an institution that is formed and tasked with overseeing business competition, the institution referred to is the Business Competition Supervisory Commission (KPPU) which was formed to oversee the implementation of Law Number 5 of 1999 concerning Prohibition Monopolistic Practices and Unfair Business Competition. These provisions are further regulated through Government Regulation Number 17 of 2013 concerning the implementation of Law no. 20 of 2008 concerning MSMEs which confirms KPPU as the supervisor of partnerships. This authority provides another alternative for the parties to settle cases in the plasma nucleus agreement. The focus of the discussion in this article is how the KPPU supervises the Inti Plasma partnership pattern and what are the consequences of the KPPU's decision on the nucleus plasma agreement for oil palm plantations using normative juridical methods. The results of the discussion show that the KPPU's authority in supervising the plasma nucleus partnership is the authority of complementary state institutions (state auxiliary organs) or state institutions formed outside of the constitution and institutions that assist the implementation of the main tasks of the state (executive, legislative, judicial). The consequences of KPPU's supervision of the plasma nucleus agreement which is declared not in accordance with the law will have an impact on the validity of the agreement.Keywords: KPPU, Monitoring, Inti Plasma, Palm Oil.